The Role of 39 Psoriasis Risk Variants on Age of Psoriasis Onset. (23rd September 2013) - Lu, Yingchang; Kane, Sinae; Chen, Haoyan; Leon, Argentina; Levin, Ethan; Nguyen, Tien; Debbaneh, Maya; Millsop, Jillian W.; Gupta, Rishu; Huynh, Monica; Butler, Daniel; Cordoro, Kelly; et al.
Abstract : Recent genome-wide association studies (GWAS) have identified multiple genetic risk factors for psoriasis, but data on their association with age of onset have been marginally explored. The goal of this study was to evaluate known risk alleles of psoriasis for association with age of psoriasis onset in three well-defined case-only cohorts totaling 1, 498 psoriasis patients. We selected 39 genetic variants from psoriasis GWAS and tested these variants for association with age of psoriasis onset in a meta-analysis. We found that rs10484554 and rs12191877 near HLA-C and rs17716942 near IFIH1 were associated with age of psoriasis onset with false discovery rate < 0.05. The association between rs17716942 and age of onset was not replicated in a fourth independent cohort of 489 patients (P = 0.94 ). The imputed HLA-C*06:02 allele demonstrated a much stronger association with age of psoriasis onset than rs10484554 and rs12191877. We conclude that despite the discovery of numerous psoriasis risk alleles, HLA-C*06:02 still plays the most important role in determining the age of onset of psoriasis. Larger studies are needed to evaluate the contribution of other risk alleles, including IFIH1, to age of psoriasis onset.